A Case Report and Literature Review on Mucinous Adenocarcinoma of the Colon in Uganda - Richard Wismayer (Highlights on Medicine and Medical Science Vol. 7, 2021)
Introduction: In Uganda, the Kampala Cancer Registry has reported a steady increase in the incidence of colorectal carcinoma (CRC) over the last few decades. The author reports a case of a 25 year old gentleman presenting with bowel obstruction and found to have mucinous adenocarcinoma of the colon. This is followed by a literature review of the clinical and pathological characteristics of young age sporadic colorectal carcinoma (YSCC) and hereditary nonpolyposis colorectal carcinoma (HNPCC). Presentation of Case: This patient presented with a family history of colorectal carcinoma (CRC) and with bowel obstruction. An emergency laparotomy involving a right hemicolectomy was carried out. The postoperative course of this patient was uneventful. Discussion: The typical histological features of mucinous adenocarcinoma of the colon were seen on the resected colon specimen. In addition this study reviews the literature regarding the clinical presentation, pathological characteristics, histology and prognosis of mucinous and medullary carcinoma of the colon. Conclusions: Mucinous adenocarcinoma happens to be the most common histological type of colorectal carcinoma in young adults. In Uganda, low risk young patients with symptoms should be screened for colorectal lesions. A high index of suspicion should therefore be taken in the diagnosis of colorectal malignancy in these patients.